The Change of Concept: the Formation and Reflection of Applied Ethnomusicology - Hanshi, Bao; Sularso, Sularso; Clarisse, Marie-Christinne B (Gelar: Jurnal Seni Budaya, 2021)
If the study of Jesse Fewkes and Frances Densmore in the late 19th century is taken into account, western Applied Ethnomusicology is entering its second century. After more than one hundred years of development, Applied Ethnomusicology has basically become a relatively mature research path in the West, which not only provides scholars with a new research perspective but also enriches the subject connotation of Ethnomusicology to a certain extent with its research philosophy and value pursuit. In China, Applied Ethnomusicology has attracted more and more attention. Therefore, reviewing the development history of the discipline is not only conducive to clarifying the development context of the discipline but also conducive to reflecting on the current problems and better grasping the development trend of the discipline. In the first part of this paper, the factors influencing the birth and development of applied ethnomusicology are further discussed from within and outside the discipline, respectively based on consulting relevant literature and briefly summarizing the existing discussions of scholars. The second part mainly discusses the research characteristics of Applied Ethnomusicology, such as "pragmatic orientation", "change of researcher's identity", and "emphasis on intervention and intervention". The third part of the Applied Ethnomusicology on the "intervention", "the definition of" discipline "and the edge of two issues are discussed.